Fretting fatigue on thin sheets - Gaertner E.L.* (2015)
© (2015) Trans Tech Publications, Switzerland.The fretting is responsible for many failures of components in the industry. It is present in assemblies like rivet and screw fixture, dovetail joint, shaft and hub with key, and all connections of two bodies with a contact force and a small induced relative displacement. Topic of studies for decades, the researchers perform experimental tests with some simplification in order to accelerate the phenomenon, some times using standard devices or creating dedicated machines for better representing the behavior of the desired components. There are a few studies with thin sheets, in which the fretting fatigue has more impact because a small reduction of the cross section due to the wear of crack results in a significant increase of stress and rate of crack propatation, decresing the number of cycles until failure. In this work, it was build a device to generate the fretting fatigue with two different shape of contact pad. The specimen is a stainless steel sheet thickness 0.152mm, which fractures and surfaces were analyzed using the SEM and white light interferometer to understand the fractures.